Screening and management of thyroid dysfunction in preterm infants - Hye Rim Chung (Korean Society of Pediatric Endocrinology, 2019)
Preterm infants can suffer various thyroid dysfunctions associated with developmental immaturity of the hypothalamic-pituitary-thyroid axis, postnatal illness, medications, or iodine supply. The incidence of thyroid dysfunction among preterm infants is higher than that among term infants and has been increasing with improvement in the survival of preterm infants. Hypothyroxinemia is frequently observed during the first week of life in extreme preterm neonates, and the incidence of delayed thyrotropin elevation is high at the age of 2-6 weeks. Although the necessity of routine rescreening remains controversial, recent guidelines on screening for congenital hypothyroidism have recommended rescreening of all preterm neonates. Thyroid hormone replacement is recommended for persistent thyrotropin elevation with or without hypothyroxinemia. Hypothyroxinemia without thyrotropin elevation does not require treatment, and some potential risks of levothyroxine supplementation have been reported. Although most thyroid dysfunctions are transient, careful follow-up after discontinuation of levothyroxine is considered so as to avoid missing persistent hypothyroidism.